PtPdAg Hollow Nanodendrites: Template‐Free Synthesis and High Electrocatalytic Activity for Methanol Oxidation Reaction. Issue 1 (19th November 2019) - Zhang, Tao; Sun, Yiqiang; Li, Xuejiao; Li, Xinyang; Liu, Dilong; Liu, Guangqiang; Li, Cuncheng; Fan, Hong Jin; Li, Yue
Abstract: To boost the electrocatalytic activity of metal nanoparticles, it is important to rationally design the composition and surface atomic structure, and develop efficient synthesis protocols. Herein, a facile one‐pot self‐templated method for preparing PtPdAg hollow nanodendrites (HNDs) is deployed. These HNDs possess rich atomic steps and grain boundaries, leading to evidently higher catalytic activity in methanol electrooxidation reaction than commercial Pt black and solid particles with smooth surfaces. From control experiments and density functional theory calculations, it is proven that the tri‐metallic HND has a stronger electronic coupling as compared with the PtPd and PtAg nanoparticles. As a result, the PtPdAg HNDs show high anti‐poison capability and catalytic activity for methanol oxidation reaction. This study provides a new strategy for controllable synthesis of hollow alloy nanocatalysts with high efficiency. Abstract : PtPdAg hollow nanodendrites with tunable compositions are made easy by a one‐step synthetic method, and they show greater catalytic activity for methanol oxidation reaction than commercial Pt black. It is proposed that atomic defects play an important role in the catalyst activity.